The Wadsworth guide to research - Miller-Cochran, Susan K.; Rodrigo, Rochelle L. (Wadsworth, 2011)
Encourages users to consider the impact of their audience, purpose, and context at every stage of the research process. This title offers coverage of the 'how' and 'why' of researching, and the key research technologies important to success.